Analisis dan Perancangan Aplikasi Bee-Messenger Sebagai Media-Media Instant Messanging di Universitas Bina Nusantara - Eddy Santosa Jaya; Irawan Irawan; Regan Regan; Indahwati Indahwati (ComTech: Computer, Mathematics and Engineering Applications, 2010)
Technology today has progressed at a rapid rate, as well as with instant messaging growing into all aspects of life, even more so in the advancement of communication technology. By using the VoIP feature, users can communicate by voice via the Internet. Messenger as a communication medium that is fast, accurate and low cost is expected to meet the need for a practical communication media. The purpose of this study is to analyze and design a messaging application called Bee-Messenger which will be used as a medium of instant messaging in Bina Nusantara University, and also analyze the needs of users with feature-contained in commonly used messenger applications. Research methods used are literature review, field studies, and field observations. Evaluation is based on the comparison of Bee-Messenger features with the same features found in Yahoo Messenger and MSN Messenger. Bee-Messenger can also activate YM and MSN messaging accounts simultaneously in a single application that gives users a practical application messaging.